Control constraint‐based optimal PID‐PSS design for a widespread operating power system using SAR algorithm - A.S.V., Vijaya Lakshmi; Mangipudi, Siva Kumar; Manyala, Ramalinga Raju (International transactions on electrical energy systems, 2021)
Summary Nowaday's tuning of a power system stabilizer (PSS) over widespread operating conditions to safeguard the power system stability is a challenging task to power engineers. Therefore, there is a need to develop a robust and reliable PSS to produce clean and sustainable energy for power generation. In this research work, a control constraint‐based optimal proportional, integral, and derivative (PID)‐PSS using nature‐inspired search optimization technique called search‐and‐rescue algorithm (SAR) is developed to suppress the low‐frequency oscillations (LFOs) in a power system operating in a wide range of operational states. The wide variations in the system operating conditions are captured by the coefficients of interval polynomial and then simple inequality conditions are attained to assure the power system stability. Furthermore, a multi‐objective function (MOF) is formulated to enhance the operation of the proposed PID‐PSS for a widespread operating state and also to encounter practical working conditions. A human search‐based optimization algorithm, that is, SAR, is implemented to acquire the PID‐PSS gains. The design resilience of the proposed PID‐PSS is investigated using two test cases of a one‐machine infinite‐bus (OMIB) power system operating at a widespread and also verified for static and dynamic mechanical disturbances. The simulation results show that the proposed optimal PID‐PSS controller outperforms the most prominent controllers in the recent literature. Synchronous generators connected by weak tie lines or under stressed conditions when subjected to small disturbances cause LFOs, which may sustain or grow in size and leads to instability. The addition of PID‐PSS modulates the excitation signal and preserves the system stability. Simple five inequality constraints and multi‐objective function are developed in terms of PID‐PSS gains to ensure robust stability of a widespread operating power system. The optimal design of PID‐PSS is carried out using search‐and‐rescue optimization algorithm.